Nutriosomes: prebiotic delivery systems combining phospholipids, a soluble dextrin and curcumin to counteract intestinal oxidative stress and inflammation. Issue 4 (10th January 2018) - Catalán-Latorre, Ana; Pleguezuelos-Villa, Maria; Castangia, Ines; Manca, Maria Letizia; Caddeo, Carla; Nácher, Amparo; Díez-Sales, Octavio; Peris, José Esteban; Pons, Ramon; Escribano-Ferrer, Elvira; Fadda, Anna Maria; Manconi, Maria
Abstract : Nutriosomes, new phospholipid nanovesicles specifically designed for intestinal protection, have been developed. Abstract : Nutriosomes, new phospholipid nanovesicles specifically designed for intestinal protection were developed by simultaneously loading a water-soluble dextrin (Nutriose® FM06) and a natural antioxidant (curcumin). Nutriosomes were easily fabricated in a one-step, organic solvent-free procedure. The stability and delivery performances of the vesicles were improved by adding hydroxypropyl methylcellulose. All the vesicles were small in size (mean diameter ∼168 nm), negatively charged (zeta potential ∼−38 mV, irrespective of their composition), and self-assembled predominantly in unilamellar vesicles stabilized by the presence of Nutriose®, which was located in both the inter-lamellar and inter-vesicle media, as confirmed by cryo-TEM and SAXS investigation. The dextrin acted also as a cryo-protector, avoiding vesicle collapse during the lyophilization process, and as a protector against high ionic strength and pH changes encountered in the gastrointestinal environment. Thanks to the antioxidant properties of curcumin, nutriosomes provided an optimal protective effect against hydrogen peroxide-induced oxidative stress in Caco-2 cells. Moreover, these innovative vesicles showed promising efficacy in vivo, as they improved the bioavailability and the biodistribution of both curcumin and dextrin upon oral administration, which acted synergically in reducing colonic damage chemically induced in rats.